2020
DOI: 10.3389/fgene.2020.00079
|View full text |Cite
|
Sign up to set email alerts
|

Association of TGF-β1, IL-4, and IL-10 Polymorphisms With Chronic Kidney Disease Susceptibility: A Meta-Analysis

Abstract: Background: Anti-inflammatory cytokine polymorphisms in the transforming growth factor-b1 (TGF-b1), interleukin-4 (IL-4), and IL-10 genes have been implicated as risk factors for chronic kidney disease (CKD), but the results from published studies are inconsistent. Our meta-analysis reviews and summarizes the cumulative evidence for these associations. Methods: A systematic literature search of five databases was performed up to October 2019. Two authors independently extracted data and evaluated the quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…They reported a highest OR of 4.16 (2.92-5.94) among the other studies, which was also comparatively very high than our study [28]. Another recent meta-analysis study by Mai et al, 2020 has also proved the association of TGFβ1 polymorphism (rs18000471) in the development of chronic kidney diseases [29].…”
Section: Discussionsupporting
confidence: 43%
“…They reported a highest OR of 4.16 (2.92-5.94) among the other studies, which was also comparatively very high than our study [28]. Another recent meta-analysis study by Mai et al, 2020 has also proved the association of TGFβ1 polymorphism (rs18000471) in the development of chronic kidney diseases [29].…”
Section: Discussionsupporting
confidence: 43%
“…A recent study suggested that genetic variants in the TGF-β1 and IL-4 genes rs1800469, rs1800470, rs1800471, and rs8179190 may play a role as a genetic contributor to the susceptibility of chronic kidney disease [10]. In addition, TGF β1 was found to induce renal hypertrophy and fibrosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…It has three closely related isoforms TGF-β1, TGF-β2 and TGF-β3. TGF-β has dual effects, which are pro-inflammatory and anti-inflammatory, with a pronounced immunosuppressive effect [10]. TGF-β1, -β2, and -β3 share 71-80% sequence identity and signal through the same receptors [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation